Upaya Meningkatkan Hasil Belajar Seni Tari Menggunakan Metode Tutor Sebaya Di Kelas X SMK Pariwisata ‘Aisyiyah Sumatera Barat - Siti Mudrika; Susmiarti Susmiarti (Institut Nalanda, 2023)
This look at aims to discover and describe how efforts to enhance dance learning results the use of the peer show method in magnificence X Tourism Vocational school 'Aisyiyah West Sumatra. This sort of studies is school room movement studies (automobile). This classroom movement research makes use of qualitative methods using descriptive methods. The difficulty of this research turned into elegance X Culinary and Hospitality at Tourism Vocational college 'Aisyiyah West Sumatra, with a total of 18 students. This study carried out the peer tutoring method in getting to know the Indang creation dance which turned into accomplished in two cycles. the first cycle includes 3 meetings and the second one cycle includes 2 meetings. The research tool used observation sheets of students' observations in getting to know, whilst to discover the boom in college students' competencies used evaluation / check sheets. The effects of the look at confirmed that there has been an increase in scholar studying consequences the use of the peer tutoring technique for class X students at Tourism Vocational college 'Aisyiyah West Sumatra. this may be seen from the percentage of students' mastering sports and their learning results. In cycle I the percentage of students' fantastic learning sports become 55% and negatively 45% and in cycle 2 the proportion of students' nice learning sports rose to eighty three% and the poor decreased to 17%. scholar studying consequences also increase by using the use of this peer tutoring method. increased mastering effects of students in which in cycle I the average price of students turned into 60.5 with a percent of completeness of 44% and 56% incomplete, this skilled an increase in cycle II where the average fee of college students rose to 77.2 with a complete percent of 88.nine% entire and 11.1% incomplete.